How to Survive in Book Store Industry through Strengthening Brand Equity - Evita Sukmawati; Leonnard Ong (Sekolah Tinggi Manajemen IPMI, 2019)
This study aims to determine the influence of corporate positioning on brand equity. Data were obtained from the result of filling out questionnaires by 200 respondents who were all consumers of Gramedia Book Stores. The data were analyzed descriptively and quantitatively through Structural Equation Modelling (SEM) analysis. The findings revealed that the corporate positioning of the Gramedia Book Stores has a positive and significant effect on consumer brand equity. Further managerial implications are provided.